Healing Justice, Transformative Justice, and Holistic Self-Care for Social Workers. Issue 2 (1st April 2020) - Pyles, Loretta
Abstract: A self-care movement for social workers is beginning to embrace mindfulness and other forms of wellness. However, self-care is often framed as merely an individualistic pursuit and may be a tool of managerialism, reinforcing the social and economic structures and culture that are causing burnout and moral injury in the first place. Particularly for people who are marginalized, the self-care movement may ignore historical trauma and the ways that interlocking oppressions contribute to stress, trauma, moral injury, and burnout. Drawing from the evidence base on East–West mind–body practices and informed by a transformative practice lens, healing justice is presented as a framework and set of practices of the whole self. The whole self includes the physical, emotional, mental, spiritual, social, and ecological selves. A transformative approach to healing can be supported by enhancing the capabilities of mindfulness, compassion, curiosity, critical inquiry, effort, and equanimity. The concept of the healing justice organization is introduced as an opportunity for organizational change beginning with a set of inquiries for social work organizations to attend structurally and more purposefully to collective care.